(untitled) (Biological Sciences - PJSIR, 2006)
The effect of different carbon sources, namely, sawdust and powder of agrowastes (as such, or water soluble extracts), and inorganic/natural nitrogen sources on the biomass production of Pleurotus sajor-caju by submerged culture fermentation was studied. Supplementation of the fermentation medium with 2% molasses, 2% wheat spike powder, extract of 2% wheat spike powder, and corn gluten meal resulted in 12.85, 10.85, 12.35 and 13.92 g/l biomass production of P. sajor-caju, respectively. The fungal hyphae biomass contained 8.28% moisture, 21.18% crude pro- tein, 1.55% fat, 3.59% ash, 2.32% crude fibre, and 63.48% nitrogen free extract